O inventário do patrimônio arquitetônico enxaimel da área rural de Santo Cristo - Diel, Rocheli Andréia (2015)
The architectural heritage provides the community the knowledge about its past as it retains its history, once that the urban landscape is one of the physical representations of the city's identity and its inhabitants. The architecture is a main manifestation for the cities history analysis and understanding, because the buildings are important means of recognition and urban reference. The building, an architectural heritage category, is very present in the daily life of a community, it is an important means of cultural appreciation over the generations. It is emphasized that before any preservationist action it is essential to identify and collect all relevant information of the heritage assets to be protected. The inventory stands as an effective means of preservation, because besides the documentation, it is able to keep the collective memory, providing the heritage assets respect and appreciation. So, the general objective of this survey is to develop the inventory of the Enxaimel architectural heritage in the countryside of Santo Cristo, by searching buildings related the city formation and which are characterized by the use of the enxaimel technique. In order to catalog the buildings, the inventory records used by IPHAE have been used and the selection criteria were beyond the time frame (1910-1960), its Cultural-Historical and Architectural-Morphological relevance. There have been inventoried twelve buildings in the countryside of Santo Cristo, based on the physical buildings survey, their particularities records, constructive characteristics, technical photographic analyses. From these analyzes the Patrimonial Memory Game was made the aimed at the heritage spreading and appreciation. As a conclusion, it is intended to contribute to the knowledge building and the heritage dissemination to the community as it is being unnoticed, as a consequence rescuing the urban and rural memories, contributing to the development of new public policies.